Teaching Mathematics to Early Graders During Lockdown in Delhi: A Challenge - Teotia, Anil (THE PRIMARY TEACHER, 2022)
The COVID-19 pandemic is going to kill the sensitive and critical period of mathematical learning. This pandemic is leading towards a learning crisis. The continuous closure of schools is going to affect the learning process of first and second graders in negative ways. This adversity faced by the education system now is going to seriously affect us in silent ways. The “early years” suffered a lot. This has inspired the researcher to examine the effects of the lockdown on the teaching and learning of mathematics with regard to early graders in Delhi. Many classes were observed, and parents, teachers, and School Management Committee (SMC) members were interviewed to understand the real issues and challenges. The COVID-19 pandemic was unprecedented and never expected to be one of the most significant pandemics of the modern era. It led to the closure of schools and a paradigm shift in the way learning is accessed. This shift was made with almost zero planning. The apps made in western countries to complement their education systems were adopted in India without a single alteration. Teaching mathematics online to early-year learners is problematic. Among the challenges that were found, the major one was the short attention span of the children. Others include the complicated manner of reaching out to children, and uneven access to technology.